PENGARUH KOMPETENSI PEDAGOGIK, KOMPETENSI PROFESIONAL, DAN KOMPETENSI SOSIAL TERHADAP KINERJA GURU SD DI WILAYAH GUGUS II KAPANEWON PANJATAN - Sri Suharyanti; Supriyoko; Rejokirono (STKIP Subang, 2023)
Teachers should be able to carry out their performance properly in accordance with the competency standards they must have, namely pedagogic competence, professional competence, and social competence. The results from UKG are that there are still many teachers who have low grades, prepare monotonous lessons, some have difficulty communicating with parents.This study aims: 1) Knowingthe influence of pedagogical competence on the performance of elementary school teachers in the Cluster II Kapanewon Panjatan area 2) To find out the effect of professional competence on the performance of elementary school teachers in the Cluster II Kapanewon Panjatan area. 3) Knowing the effect of social competence on the performance of elementary school teachers in the Cluster II Kapanewon Panjatan area 4) Knowing the effect of pedagogic competence, professional competence, and social competence together on the performance of elementary school teachers in the Kapanewon Panjatan area.This research uses quantitative methods. Methods of data collection with questionnaires and documentation. The population in this study were elementary school teachers in the Cluster II Kapanewon Panjatan area, totaling 64. The sample was taken using a probability sampling technique with cluster random sampling type. The sample used was 30 people. Hypothesis testing using multiple linear regression analysis test, partial test (t test), regression coefficient test together (F test). The classic assumption test is the normality test, linearity test, multicollinearity test, heteroscedasticity test. All calculations are processed using the SPSS version 25 program. The results showed: Yespositive and significant effect of pedagogical competence on the performance of elementary school teachers in the Cluster II Kapanewon Panjatan area of ​​17.13% 2) There is a positive and significant effect of professional competence on the performance of elementary school teachers in the Cluster II Kapanewon Panjatan area of ​​58.15% 3) There is a positive and significant effect social competence on the performance of elementary school teachers in the Cluster II Kapanewon Panjatan area of ​​24.72% 4) There is a positive and significant effect of pedagogic competence, professional competence, and social competence together on the performance of elementary school teachers in the Kapanewon Panjatan area.